Effect of Intrinsic Layer Energy Gap and Thicknesses Optimization on the Efficiency of p-i-n Amorphous Silicon Solar Cell - Ignatio Benigno; Darminto Darminto (IPTEK Journal of Science, 2017)
morphous silicon solar cells with single p-i-n layer were grown on 10 cm2 ITO coated glass substrates. Fabrication process done by using 13.56 MHz RF-Plasma Enhanced Chemical Vapor Deposition (PECVD). Hydrogen flow on the deposition process is widely known to enable the passivation of the dangling bond on Silicon bonds. The passivation of dangling bond affects the band gap of each layer and cell performance in the absorption of photon. In the deposition process of intrinsic layer, SiH4 gas flow is set constant at 2.5 sccm, while variation is done in hydrogen gas flow at 0 sccm – 90 sccm. Energy gaps obtained for p-layer and n-layer are 2.0 eV and 2.2 eV at thickness 64 nm and 36 nm respectively. Optimizations have been done for intrinsic layer which band gaps are 1.4 eV, 1.6 eV and 1.9 eV at thickness 400 nm. The solar cell efficiency was increased from 4.8% to 5.64% based on the band gaps variety. In addition, i-layer thicknesses were also varied from 400 nm, 500 nm and 600 nm. Thicknesses variation shows an increase of 5.78% in the solar cell efficiency.